أثر الاعتماد الأكاديمي في فاعلية الأداء المدرسي - عبد الرحمان السعودي, شريف; بن علي عسيري, عبد الله (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى معرفة درجة تأثير الاعتماد الأكاديمي على فاعلية الأداء في مدارس الهيئة الملكية بالجبيل، من وجهة نظر قياداتها. إذ تكونت عينة الدراسة من (40) مديراً ووكيلاً، في العام الدراسي 2019/2020، وخلصت نتائج الدراسة إلى أن مشروع الاعتماد الأكاديمي كان له أثراً إيجابياً على جميع مجالات الدراسة، إذ كانت جميعها في المستوى المرتفع، حيث تراوحت قيم المتوسطات الحسابية لاستجابات قيادات المدارس المستهدفة على الاستبانة للمجالات الستة بين (3.60-4.02) وبنسب مئوية تراوحت بين (72%-80%)، كما أظهرت النتائج وجود فروق دالة إحصائياً في درجة تأثير الاعتماد الأكاديمي تعزى لمرحلة المدرسة، ولصالح المدارس الثانوية. Abstract: This study aimed to explore the degree of the effect of academic accreditation on the effectiveness of performance in the schools of the royal commission in Jubail, from the viewpoint of its leaders. The study sample consisted of (40) director and agent, in the academic year 2019/2020, the results of the study indicate that the academic accreditation had a positive impact on all areas of study it was at the high level, where the values of the mean ranged for the school leaders' responses for the six domains between (3.60-4.02) and percentages ranged between (72%-80%), and as is the results were a show of statistically significant differences in the degree of the effect of academic accreditation to the variable of school level and for the benefit of secondary schools.
مقال
Keywords: الاعتماد الأكاديمي ; فاعلية الأداء المدرسي ; مدارس الهيئة الملكية بالجبيل ; منظمة ادفانس-إيد; Academic accreditation; School performance; Jubail Royal Commission schools